Quality of HIV Care and Mortality in HIV-Infected Patients. - Korthuis, P Todd; McGinnis, Kathleen A; Kraemer, Kevin L; Gordon, Adam J; Skanderson, Melissa; Justice, Amy C; Crystal, Stephen; Goetz, Matthew Bidwell; Gibert, Cynthia L; Rimland, David; Fiellin, Lynn E; Gaither, Julie R; et al. (Clinical infectious diseases : an official publication of the Infectious Diseases Society of America, 2015)
The Patient Protection and Affordable Care Act encourages healthcare systems to track quality of care (QOC) measures; little is known about their impact on mortality. The objective was to assess associations between HIV QOC and mortality.